Analysis of cases and accuracy of 3 risk scoring systems in predicting ectasia after laser in situ keratomileusis. Issue 8 (August 2018) - Chan, Cordelia; Saad, Alain; Randleman, Bradley J.; Harissi‐Dagher, Mona; Chua, Daniel; Qazi, Mujtaba; Saragoussi, Jean‐Jacques; Shetty, Rohit; Ancel, Jean‐Marc; Ang, Robert; Reinstein, Dan Z.; Gatinel, Damien
Abstract : Purpose : To identify risk factors for ectasia after laser in situ keratomileusis (LASIK) by comparing the accuracy of the Ectasia Risk Score System (ERSS), Screening Corneal Objective Risk of Ectasia (SCORE) Analyzer, and percentage of tissue altered (PTA) in predicting the occurrence of ectasia. Setting : Multiple centers in 8 countries. Design : Retrospective case series. Methods : Previously unpublished post‐LASIK ectasia cases were analyzed. Consecutive patients who had LASIK performed at least 5 years previously with no resultant ectasia were used as controls. Axial maps from preoperative Orbscan IIz topographies were analyzed in a masked fashion, and examination files tested with the SCORE Analyzer. The PTA values and ERSS scores were generated using available preoperative and perioperative data. Only eyes with subjectively identified normal preoperative topography were tested with the PTA. Threshold values for the SCORE, ERSS, and PTA were more than or equal to 0, 4, and 40, respectively. Results : Ectasia occurred in 31 eyes (22 patients); 79 eyes (44 patients) were used as controls. In all eyes, the sensitivity and specificity for predicting ectasia, respectively, were 67.7% and 79.7% for the ERSS and 64.5% and 100% for the SCORE. In eyes with normal topography (ectasia group, 12 eyes; controls, 64 eyes), the PTA yielded sensitivity of 33.3% and specificity of 85.9%. The area under the receiver operating characteristic curve was highest for SCORE (0.911) followed by the ERSS (0.844) and PTA (0.557). Conclusions : The SCORE was most predictive of ectasia, achieving the best specificity; the ERSS had the best sensitivity. Further studies are required to validate the PTA as a screening metric for ectasia.